PENGARUH KUALITAS LAYANAN DAN DIVERSIFIKASI PRODUK TERHADAP KEPUASAN NASABAH BANK BRI KANTOR CABANG JAKARTA VETERAN - Eka Puspita Nurmaya; Hotman Napitupulu (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2021)
To determine the effect of service quality and product diversification on customer satisfaction Bank BRI at the Jakarta Branch Office Veterans. The research method uses descriptive qualitative and quantitative analysis, the analytical model used is linear regression, simultaneous and partially. The research population is Bank BRI customers at the Jakarta Branch Office Veterans who visit from April to June 2021. Result the simultaneous, service quality and product diversification have a significant effect on customer satisfaction at Bank BRI Jakarta Veterans Branch Office. Partially service quality has a positive and significant effect on customer satisfaction, and partially product diversification has a positive and significant effect on customer satisfaction.